Utility of Plasmodium falciparum DNA from rapid diagnostic test kits for molecular analysis and whole genome amplification - Srisutham, S; Suwannasin, K; Mathema, VB; Sriprawat, K; Smithuis, FM; Nosten, F; White, NJ; Dondorp, AM; Imwong, M (BioMed Central, 2020)
Background Rapid diagnostic tests (RDTs) have become the most common diagnostic tool for detection of Plasmodium falciparum malaria, in particular in remote areas. RDT blood spots provide a source of parasite DNA for molecular analysis. In this study, the utility of RDTs for molecular analysis and the performance of different methods for whole genome amplification were investigated.